Electronic skins for soft, compact, reversible assembly of wirelessly activated fully soft robots - Byun, Junghwan; Lee, Yoontaek; Yoon, Jaeyoung; Lee, Byeongmoon; Oh, Eunho; Chung, Seungjun; Lee, Takhee; Cho, Kyu-Jin; Kim, Jaeha; Hong, Yongtaek (AMER ASSOC ADVANCEMENT SCIENCE, 2018)
Designing softness into robots holds great potential for augmenting robotic compliance in dynamic, unstructured environments. However, despite the body's softness, existing models mostly carry inherent hardness in their driving parts, such as pressure-regulating components and rigid circuit boards. This compliance gap can frequently interfere with the robot motion and makes soft robotic design dependent on rigid assembly of each robot component. We present a skin-like electronic system that enables a class of wirelessly activated fully soft robots whose driving part can be softly, compactly, and reversibly assembled. The proposed system consists of two-part electronic skins (e-skins) that are designed to perform wireless communication of the robot control signal, namely, "wireless inter-skin communication," for untethered, reversible assembly of driving capability. The physical design of each e-skin features minimized inherent hardness in terms of thickness (<1 millimeter), weight (-0.8 gram), and fragmented circuit configuration. The developed e-skin pair can be softly integrated into separate soft body frames (robot and human), wirelessly interact with each other, and then activate and control the robot. The e-skin-integrated robotic design is highly compact and shows that the embedded e-skin can equally share the fine soft motions of the robot frame. Our results also highlight the effectiveness of the wireless interskin communication in providing universality for robotic actuation based on reversible assembly.
Keywords: STRETCHABLE ELECTRONICS; DESIGN; FABRICATION; SENSORS